EFL Learners’ Feedback on The Use of Short Movies in English Speaking Classroom - Angraini, Nike (Wanastra: Jurnal Bahasa dan Sastra, 2025)
The Current investigation was intended to see the feedback of EFL learners on the application of short movies in English-speaking classrooms. An experimental research design was consciously chosen, which primarily concerned descriptive statistical analysis. Fourteen samples were taken purposefully. To measure the EFL learners’ feedback, the distribution of questionnaire items set was utilized. Twenty-one items were designed to seek the aspects of psychology, linguistics, and literature. The findings revealed that positive feedback was made by the participants viewed from a psychological viewpoint (English learning preference, motivation, enthusiasm, and bravery). In addition, positive feedback was also earned by the majority of the EFL learners on their English-speaking aspects seen from a linguistics viewpoint (pronunciation, vocabulary, content, grammar, and fluency), excluding intonation. Besides, positive feedback was possessed by some other EFL learners concerned on literature viewpoint (generating moral lesson, understanding sequence of movie events, speaking and writing, as well as analyzing movie event), excluding story plot. Some following parties limited to English teachers, EFL students, stakeholders, and other researchers were offered several pedagogical implications.